Economic Factor on the In Situ Vanillin Enzymatic Formation from the Green Pods Vanilla - Hartati, Indah; Ardi, Pradipta Risma Rukma; Milzam, Muhammad; Paramita, Vita (Vocational College of Universitas Diponegoro, 2019)
This work proposed a study of a direct enzymatic of vanillin formation by using rumen liquid which has enzymatic capability for tissue disruption of vanilla green pods to avoid the curing process. Application of enzymes during the formation of vanilla aromas and its extraction present nice opportunity to improve productivity, as the enzymatic reaction possibly substitute the microbial process in the traditional fermentation. Green vanilla pods were applied for the direct enzymatic extraction of vanillin, while liquid rument provide cell wall degrading enzyme in order to support the hydrolysis process (destruction) of cell wall. Glucovanillin were contacted with the β-glucosidase in the green pods due to the desruction of the cell wall, followed by the formation of glucovanillin into vanillin. Vanillin content of vanilla green pods was found higher in which by treating the vanilla green pods at 30 °C.